Mechanical behaviour of micro-alloyed steels with vanadium for rail axles - D.E.P. Klenam; L.H. Chown; M.J. Papo; L.A. Cornish (Hybrid Advances)
Mechanical and microstructural characterisation after different treatments of three new experimental micro-alloyed steels with vanadium for potential use as rail axles was undertaken. The quenched and tempered alloys had yield strengths from 668-1158 MPa and ultimate tensile strengths (UTS) from 880-1306 MPa. For the normalised and furnace-cooled alloys, the yield strengths were from 389-490 MPa with corresponding ultimate tensile strengths of 679–706 MPa. Although the strengths of the normalised and furnaced-cooled alloys were lower than the quenched and tempered, and the normalised in air alloys, they were higher than most of the standard conventional grades with minimum yield strength of 330 MPa and 600 MPa UTS. The quenched and tempered microstructures were mainly lath martensite and ferrite, with some bainite. All normalised and air-cooled steels, as well as the furnace-cooled 0.13 wt% V and 0.25 wt% V steels, were mainly bainite and ferrite. The normalised and furnace-cooled steels without V had banded ferrite-pearlite. The higher strengths of the quenched and tempered steels were due to the high proportions of martensite and bainite. The normalised and air-cooled and the normalised and furnace-cooled steels showed moderate strengths with elongations between 17% and 19% due to the ferrite-bainite or ferrite-pearlite microstructures. All steels with 0.13–0.25 wt% V had coarse microstructures but showed potential for rail axle applications due to superior mechanical properties than most standard grades.